Concentration and inorganic elemental analysis of particulate matter in a road tunnel environment (Žilina, Slovakia): Contribution of non-exhaust sources - Jandacka, Dusan; Durcanska, Daniela; Cibula, Robert (Frontiers in Environmental Science, 2022)
Particulate matter (PM) is present in the surrounding air. The tunnel environment is no exception, where the PM source is road traffic. In a broader sense, the tunnel can be described as a separate point source of air pollution from which PM pollutants spread to the portal parts and the external environment. PM originates from the exhaust and non-exhaust processes of road traffic (brake wear, tire wear, road surface wear, and road dust resuspension). This study deals with the specification of non-exhaust PM emissions in a tunnel environment where the primary source is road traffic. PM measurements took place in the “Považský Chlmec” highway tunnel with a length of 2118 m, directly in the tunnel tube and near the tunnel portal. PM measurements were performed using gravimetric and optical methods. PM chemical analyses were performed using energy-dispersive X-ray fluorescence (EDXRF). The concentration of PM in the tunnel was on average: PM10 = 30.76 µg/m3, PM2.5 = 15.66 µg/m3 and near the tunnel portal PM10 = 14.38 µg/m3 and PM2.5 = 8.74 µg/m3. The average traffic volume in the tunnel tube was 2274 veh/24h. Using EDXRF, the main chemical elements Al, Br, Ca, Cl, Cr, Cu, Fe, K, Mg, Mn, Na, P, Si, S, Ti, and Zn were identified in the PM. Chemical element concentrations in PM10 and PM2.5 were subjected to factor analysis (FA) and principal component analysis (PCA) to determine the origin of PM. Two sources were identified for PM10 and three for PM2.5. Absolute principal component scores (APCS) in conjunction with multiple regression analysis (MRA) were used to determine the source contribution to the production of PM10 and PM2.5.